2017
DOI: 10.1021/acs.orglett.7b02287
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Benzylic Functionalizations of 3-Vinyl Benzofurans via Cascade Formal Trienamine–Vinylogous Iminium Ion Activation

Abstract: An efficient approach to construct chiral 1,1-disubstituted ethane derivatives is presented. This strategy relies on the formation of the key dearomatizative vinylogous iminium ion species through protonation of the formal trienamine intermediates between 2-(3-vinylbenzofuran-2-yl)ethan-1-ones and a chiral primary amine. An array of nucleophiles, including 4-hydroxycoumarins, indoles, etc., have been effectively assembled at the benzylic site, delivering the expected 1,1-disubstituted ethane products in modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The trienamine intermediate was transformed to the vinylogous iminium ion by ε‐protonation, which allows nucleophilic attack with 4‐hydroxycoumarins 163 to furnish the corresponding 1,1‐disubstituted ethane benzofurans 164 . The reaction proceeded with moderate to excellent yields and fair to excellent enantoselectivities (Scheme ) …”
Section: Dienones Dienals and Trienanls In Vinylogous Iminium Ionmentioning
confidence: 99%
“…The trienamine intermediate was transformed to the vinylogous iminium ion by ε‐protonation, which allows nucleophilic attack with 4‐hydroxycoumarins 163 to furnish the corresponding 1,1‐disubstituted ethane benzofurans 164 . The reaction proceeded with moderate to excellent yields and fair to excellent enantoselectivities (Scheme ) …”
Section: Dienones Dienals and Trienanls In Vinylogous Iminium Ionmentioning
confidence: 99%
“…Melchiorre and co‐workers reported that β‐3‐indolyl‐ or 3‐furyl acroleins underwent Diels–Alder reactions with activated alkenes by the formation of o ‐QDM‐embedded trienamine species (Scheme b) . We also uncovered the generation of intriguing o ‐QDMs III tethering to iminium ions from 2‐(3‐vinylbenzofuran‐2‐yl)ethan‐1‐ones, which were enantioelectively attacked at benzylic sites by diverse nucleophiles (Scheme c) . Nevertheless, the asymmetric reactions involving catalyst‐tethered dearomatizative o ‐QDMs are still relatively limited, and the expansion on substitution patterns and constructing structural diversity is also in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric aminocatalysis, by using a chiral primary or secondary amine to generate active HOMO-raised enamine or LUMO-lowered iminium ion intermediates with enolizable or unsaturated carbonyls, respectively, has been extensively explored in the field of organocatalysis . Although aliphatic-type carbonyl substrates are generally utilized in aminocatalysis, some specific aromatic or heteroaryl rings can be HOMO-raised by generating conjugated formal trienamine intermediates and participate in [4 + 2] cycloaddition or Friedel–Crafts reactions stereoselectively . Moreover, a few recent examples further demonstrate that five-membered heteroaryl (especially furyl) aldehydes can form catalyst-tethered dearomative dienamine and even polyenamine species, which significantly broaden the application potential of aminocatalysis (Scheme a) …”
mentioning
confidence: 99%